Unveiling Caesar: A Linguistic and Cognitive Exploration in Shakespearean Plays (London Journal of Research In Humanities and Social Sciences, 2024)
Utilizing the “polysemy model” of semantic change in historical linguistics, “mapping” and “conceptual integration” of metaphor, the “classical taxonomic structure” of categorization theories in cognitive linguistics, and literary conventions of structuralist poetics, this article explores Caesar’s characterization in Shakespeare’s Julius Caesar and other plays. Through an analysis of the semantic change of “Caesar” and the characters’ varying cognition within the fictional world shaped by dialogues and character interactions, the study unveils a complex portrayal produced by the negotiation between the cultural milieu and Shakespeare’s artistic pursuit. In Julius Caesar, an ambiguous yet great and unique Caesar emerges. Within two kinds of intertext, comprising characters’ discourses scattered in other plays, Caesar’s ambiguity dissipates, and his greatness and uniqueness become more pronounced. The article concludes by connecting Shakespeare’s adept manipulation of literary conventions to the nuanced portrayal of Caesar, offering a distinctive contribution to the understanding of Shakespearean characters and Shakespeare’s literary competence.
Keywords: Modeling.; techniques; javelin throwing; individualization; ideology; Violence; Values; axiology; drama; manipulation; totalitarianism; superman; Mother child relations. Parent child relations. Premature birth.; Egypt; Fragmentation; Agricultural land holding; Socio-economic challenges.; Shakespearean plays; Caesar; semantic change; characterization; literary conventions